Evaluating the Moderating Role of Innovation and Supply Chain Strategy in Relation between Environmental Uncertainty and Organizational Performance - Morteza Ghasanfari; Hossein Hemati; Mohammad Parsa (International Journal of Supply Chain Management, 2019)
Significant effect of environmental uncertainty on organization performance and moderating effect of innovation as well as supply chain strategy has been caused to investigate the moderating role of strategic orientation and innovation in relation with the organization performance and environmental uncertainty. Based on purpose, this study is considered as practical study and in terms of data collection is categorized in the descriptive study in field type study. According to data analysis approach, this study is categorized as scientific studies. The population of this study consists of all managers and directors of active companies in the oil industry of Islamic Republic of Iran. In which, the number of 197 people was selected using the available sampling method and the Cochran formula. The data required in this study were collected using questionnaires in both interview and via mail. Data analysis has been done by using structural equation modeling and partial least squares by means of Smart-Pls software. The results show that environmental uncertainty has meaning full effects on the organization performance which these effects are positively moderated by innovation and strategic orientation.